Pengaruh Komitmen Organisasi, Karakteristik Individu, dan Lingkungan Kerja Terhadap Organizational Citizenship Behavior pada Perusahaan Otomotif XYZ - Thifa Fauzia Rachman; Harry Sardjono (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to determine how much influence organizational commitment, individual characteristics, and work environment have on organizational citizenship behavior in the XYZ automotive company. This type of research used in this research is to use quantitative methods. In this study, researchers used quantitative data with a descriptive approach and distributed questionnaires through Google Form. The sample of this study were 50 respondents who were employees of the XYZ automotive company. The results of the collected data were analyzed with the help of the SPSS 22 program and it can be concluded that organizational commitment has a positive effect on Organizational Citizenship Behavior, individual characteristics have a positive effect on Organizational Citizenship Behavior, and the work environment has a positive influence on Organizational Citizenship Behavior.